2022
DOI: 10.3389/fenvs.2022.950894
|View full text |Cite
|
Sign up to set email alerts
|

Linking human wellbeing and urban greenspaces: Applying the SoftGIS tool for analyzing human wellbeing interaction in Helsinki, Finland

Abstract: This article reviews a study into the relationships between greenspaces and the benefits to psychological, social, and physical aspects of human wellbeing achieved through interaction in the Helsinki urban region in Finland. This relationship is theorized, analyzed, and measured through the transactional paradigm of affordance theory and is operationalized through the use of a public participation geographic information system (PPGIS) questionnaire, SoftGIS, which activated the urban greenspace–human wellbeing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 172 publications
0
1
0
Order By: Relevance
“…First, a discussion of the specific HWB transactional benefits as related to respondent data is then followed by a discussion of UG multi-functionality or those UGs that provided for social, psychological, and physical wellbeing benefits simultaneously. The literature has suggested that physical contact and interaction with UGs influence HWB by providing psychological restoration, physical activity, and social connection among many other beneficial components (e.g., [67,97,98]). This research supports such findings by showing that interactions with UGs support multiple aspects of HWB.…”
Section: Discussionmentioning
confidence: 99%
“…First, a discussion of the specific HWB transactional benefits as related to respondent data is then followed by a discussion of UG multi-functionality or those UGs that provided for social, psychological, and physical wellbeing benefits simultaneously. The literature has suggested that physical contact and interaction with UGs influence HWB by providing psychological restoration, physical activity, and social connection among many other beneficial components (e.g., [67,97,98]). This research supports such findings by showing that interactions with UGs support multiple aspects of HWB.…”
Section: Discussionmentioning
confidence: 99%